Cheat and you Lose! Don't Cheat and you Lose! Reflections and Analysis of Accounting Student Data - Woodbine, Gordon; Amirthalingam, Vimala (Springer Netherlands, 2013)
During 2012 students enrolled in a Master’s management accounting unit wereinvited to complete a compulsory class quiz, which was arranged to include a mild form ofdeception allowing them an opportunity to cheat. Prior to the test students were coachedconcerning the importance of the ICMA code of ethical conduct, which formed the basis ofthe quiz. Following the test, students were made aware of the deception and asked to judgethe propriety of their actions using a research instrument based on moral intensity theory(Jones in The Academy of Management Review, 16(2), 366–395, 1991). Academic dishonesty,in its many forms is endemic in universities and in this study a significant number ofstudents take advantage of an opportunity to maximise test scores and earn an advertisedreward by cheating. Others adopted a virtuous position and opted not to use the information.As reported from an earlier investigation, Woodbine and Amirthalingam (2013) againdemonstrate the effect of cognitive dissonance (Festinger 1957) although previously theresearch instrument did not clearly differentiate between respondent types. A logisticregression of subsequent data establishes that high achievers (in terms of their test scores)are more likely to take advantage of the disclosed information to maximise scores and thatthis is somewhat offset by aspects of their moral character. Immediately following the fieldexperiment, students met to reflect on their actions. A summary of their responses isprovided, which tends to support prior evidence that many are somewhat blasé in theirattitude to this form of opportunistic behaviour. These findings have ramifications in termsof the way tertiary institutions emphasise academic excellence before moral development,while acting to manage the incidence of misbehaviour.